SPATIO-TEMPORAL DIVERSITY OF CULTURABLE MARINE BACTERIA WITH BIOACTIVE POTENTIAL IN COASTAL REGION OF SOUTHERN INDIA - ALAKNANDA SARKAR; KIRAGANDUR MANJUNATH (International Journal of Pharma and Bio Sciences, 2014)
This study highlights the spatio-temporal distribution of culturable heterotrophic marine bacteria from seven different coastal regions of southern India, with bioactive potentia. 370 bacterial isolates were screened for antimicrobial activity against fourteen strains of human bacterial pathogens, of which 31.62% isolates showed activity. Twenty isolates with highest activity were subjected to Amplified Ribosomal DNA Restriction Analysis (ARDRA) using restriction enzymes HaeIII and HinpI followed by partial 16S rRNA sequencing of nine representative OTUs. Majority of antibacterial isolates belonged to phylum proteobacteria, with representative class of Betaproteobacteria and Gammaproteobacteria, whereas other isolates included Firmicutes and uncultured bacteria. Also clustering based on Fatty Acid Methyl Ester (FAME) analysis was done for the nine representative isolates which showed resemblance in the phylogenetic tree obtained with partial 16S rRNA sequences. A distinct temporal pattern was observed in our study, but the spatial distribution was influenced more by the physico-chemical parameters than by latitude or longitude.